Studi Deskriptif tentang Faktor-Faktor yang Mempengaruhi Kepuasan Kerja Karyawan di PT Trans Jaya Papua - Devita Oktarini; Sapto Pramono; Sri Roekminiati (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to describe and analyze the factors that influence employee job satisfaction at PT Trans Jaya Papua by employing a qualitative descriptive method supported by observation and semi-structured interviews with 12 employees across different departments. The findings reveal that job satisfaction arises from a combination of internal and external factors that interact to shape employees’ overall perceptions of their work. Internal factors consist of individual attitudes, motivation, and the quality of interpersonal relationships, all of which determine how employees respond to daily tasks and workplace dynamics. External factors include leadership style, salary, work environment, and organizational support, each playing a crucial role in shaping employees’ sense of stability and fairness. The results highlight that positive work attitudes and effective communication are the most dominant contributors to employee satisfaction, strengthened by adequate compensation and supportive supervision from leaders. The study concludes that job satisfaction can be further improved through transparent communication, equitable reward systems, and consistent leadership involvement in employee development. These findings provide practical implications for management, particularly in formulating more responsive human resource strategies aimed at enhancing employee performance and organizational effectiveness.